Sonographic Evaluation of Liver Dimension among Apparently Healthy Pediatrics in Kano Metropolis, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Establishing normal liver size is critical in the diagnosis and determining the treatment method for the underlying liver pathology.Aims:This study aimed at evaluating liver dimensions of apparently healthy pediatrics using ultrasonography in Kano metropolis, Nigeria.Settings and Design:This cross-sectional study was conducted in Kano Metropolis, Nigeria, from May 2020 to August 2020.Materials and Methods:Four hundred and twenty-six apparently healthy pediatric subjects; 213 males and 213 females. The liver was examined with the patient in the supine position, the anteroposterior liver dimension was obtained in a transverse plane through the mid clavicular line from the hepatic dome to the inferior angle. Cranio-caudal liver dimension was obtained in a longitudinal plane with an oblique beam at the level where the widest diameter was demonstrated.Statistical Analysis:Both descriptive inferential statistics were employed for the data analysis. Statistical Package for the Social Sciences Version 23.0 was used for the data analysis andP < 0.05was considered significant.Result:The mean cranio-caudal liver dimension for male and female subjects were 9.28 ± 2.18 cm and 9.17 ± 2.19 cm, respectively, while the mean antero-posterior liver dimension for male and female subjects was 6.87 ± 1.92 cm and 6.74 ± 1.90 cm, respectively. A statistically significant difference between pediatric age groups was observed (p≤ 0.001). However, there was no statistically significant difference in cranio-caudal and antero-posterior liver dimensions between male and female subjects (p ≥ 0.10, 0.24, 0.66, 0.30, 0.92, 0.33, and P ≥ 0.11, 0.79, 0.69, 0.45, 0.81, 0.29for the respective pediatric age groups), respectively.Conclusion:References values for pediatric cranio-caudal and antero-posterior liver dimensions were established.